The CHAC1-inhibited Notch3 pathway is involved in temozolomide-induced glioma cytotoxicity. (April 2017) - Chen, Peng-Hsu; Shen, Wan-Lin; Shih, Chwen-Ming; Ho, Kuo-Hao; Cheng, Chia-Hsiung; Lin, Cheng-Wei; Lee, Chin-Cheng; Liu, Ann-Jeng; Chen, Ku-Chung
Abstract: Glioblastoma multiforme (GBM) is the high-grade primary glioma in adults. Temozolomide (TMZ), an alkylating agent of the imidazotetrazine series, is a first-line chemotherapeutic drug for clinical therapy. However, the expense of TMZ therapy and increasing drug resistance to TMZ decreases its therapeutic effects. Therefore, our aim was to investigate the detailed molecular mechanisms of TMZ-mediated cytotoxicity to enhance the efficacy of TMZ in clinical GBM therapy. First, TMZ-mediated gene expression profiles and networks in U87-MG cells were identified by transcriptome microarray and bioinformatic analyses. Cation transport regulator-like protein 1 (CHAC1) was the most highly TMZ-upregulated gene. Overexpression and knockdown of CHAC1 expression significantly influenced TMZ-mediated cell viability, apoptosis, caspase-3 activation, and poly(ADP ribose) polymerase (PARP) degradation. The c-Jun N -terminal kinase (JNK)1/c-JUN pathway was identified to participate in TMZ-upregulated CHAC1 expression via transcriptional control. Furthermore, CHAC1 levels were significantly decreased in GBM cell lines, TCGA array data, and tumor tissues. Overexpression of CHAC1 enhanced glioma apoptotic death via caspase-3/9 activation, PARP degradation, autophagy formation, reactive oxygen species generation, increased intracellular calcium, and loss of the mitochondria membrane potential. Finally, we also identified that TMZ significantly reduced Notch3 levels, which are upregulated in gliomas. TMZ also induced CHAC1 to bind to the Notch3 protein and inhibit Notch3 activation, resulting in attenuation of Notch3-mediated downstream signaling pathways. These results emphasize that CHAC1-inhibited Notch3 signaling can influence TMZ-mediated cytotoxicity. Our findings may provide novel therapeutic strategies for future glioblastoma therapy. Graphical abstract: Highlights: TMZ-mediated gene expression profiles and networks in U87-MG cell death. TMZ transcriptionally enhanced CHAC1 expression via JNK1/c-JUN pathway. Overexpression of CHAC1 enhanced glioma apoptotic death and autophagy formation. TMZ reduced Notch3 expression and activation in glioma. CHAC1-inhibited Notch3 activation involved in TMZ-mediated cell death.